Gallium oxide-based laminated structure ultraviolet detector and preparation method thereof

By designing a gallium oxide-based stacked structure ultraviolet detector, and using the superimposed structure to regulate electrons and holes, the problems of gallium oxide thin film defects and poor conductivity are solved, and efficient ultraviolet detection performance is achieved.

CN119767806APending Publication Date: 2025-04-04CHANGCHUN INST OF OPTICS FINE MECHANICS & PHYSICS CHINESE ACAD OF SCI
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411495835.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-25
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

Gallium oxide materials have many film defects and poor conductivity, which leads to the low application rate of traditional MSM structures on gallium oxide films and the inability to maximize their photoelectric properties.

Method used

A gallium oxide-based stacked structure ultraviolet detector is designed, including a gallium nitride single crystal substrate, a GaON film layer, a β-Ga2O3 film layer, an electron transport layer and a hole barrier layer. Through the superposition structures of these layers, electrons and holes are double-controlled to improve crystal quality and photoelectric properties.

Benefits of technology

Through the design of the stacked structure, the internal defects of the gallium oxide film are significantly reduced, the transportation efficiency of electrons and holes is improved, the inherent continuous photoconductivity effect is suppressed, and the UV light guide gain is increased, which improves the UV detection performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119767806A_ABST
    Figure CN119767806A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of semiconductor photoelectric detectors, in particular to a gallium oxide-based laminated structure ultraviolet detector and a preparation method thereof. The detector comprises a gallium nitride single crystal substrate, a GaON thin film layer and a beta-Ga2O3 thin film layer which are tightly stacked from bottom to top, and an electron transport layer and a hole blocking layer which are symmetrically arranged on the surface of one side, away from the gallium nitride single crystal substrate, of the beta-Ga2O3 thin film layer, and metal electrodes are arranged on the electron transport layer and the hole blocking layer. The material of the electron transport layer is ZnO, and the material of the hole blocking layer is TiO2. The device has the advantages that the device structure is stable, the response time can reach microsecond magnitude, and the descending time is short; the adverse effect caused by the inherent continuous photoconductive effect of the gallium oxide material is effectively overcome, the internal defects are obviously reduced, and the ultraviolet photoconductive gain is increased while the inherent continuous photoconductive effect of the gallium oxide is inhibited.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of semiconductor photoelectric detectors, and in particular to a gallium oxide-based laminated structure ultraviolet detector and a preparation method thereof. Background Art

[0002] Ultraviolet detection has a wide range of applications in military and civilian fields. Currently, the most widely used types of ultraviolet detectors on the market can be roughly divided into three types. First, in the detection of extremely weak ultraviolet rays such as space detection, vacuum photomultiplier tubes are widely used, but they can only work in high-voltage environments, and their high-temperature resistance and anti-electromagnetic interference performance are poor; secondly, silicon-based photodetectors dominate in daily life, but the bandgap width of silicon is around 1eV, and multiple filters need to be loaded when used, which is expensive. Due to the shortcomings of these two devices, ultraviolet detectors based on wide-bandgap materials were born, including diamond, silicon carbide, gallium nitride (GaN) and other group III nitrides and group II-VI oxides. Among them, detectors based on oxide materials have gradually become a research hotspot in the field of ultraviolet detection due to their excellent photoelectric detection performance, spectral response peak corresponding to the deep ultraviolet light region, high stability, and sensitive response. Gallium oxide (GaN) is a popular material for ultraviolet detection. 2 O 3 ) have become a hot material for the preparation of solar-blind ultraviolet detectors due to their natural intrinsic solar-blind absorption properties, excellent chemical and thermal stability, and relatively simple and low-cost preparation process, and have shown great application prospects.

[0003] Ga 2 O 3 There are five different crystalline phases, among which β phase is the most stable phase. β -Ga 2 O 3 Belongs to the monoclinic system, space group is C2 / m , lattice constant a =1.222nm, b =0.304nm, c =0.58nm, bond angle α = γ = 90°, β = 103.7°. Currently based on β -Ga 2 O 3The device types of thin films mainly include metal-semiconductor-metal (MSM), Schottky junction and heterojunction. Among them, the MSM type has the most reports due to its simple structure. An important problem that plagues gallium oxide materials is that the film has many defects, poor conductivity, and low electron concentration inside the film. In addition, the application rate of traditional MSM structure to gallium oxide thin films is low, which cannot maximize the photoelectric performance of gallium oxide. Summary of the invention

[0004] In order to solve the above problems, the present invention provides a gallium oxide based laminated structure ultraviolet detector and a preparation method thereof.

[0005] The first object of the present invention is to provide a gallium oxide-based laminated structure ultraviolet detector, comprising: a gallium nitride single crystal substrate, a GaON thin film layer and a β- Ga 2 O 3 The film layer, as well as the β- Ga 2 O 3 An electron transport layer and a hole blocking layer are symmetrically arranged on the surface of the thin film layer on one side away from the gallium nitride single crystal substrate; and metal electrodes are arranged on both the electron transport layer and the hole blocking layer.

[0006] Preferably, the material of the electron transport layer is ZnO, and the material of the hole blocking layer is TiO 2 .

[0007] Preferably, the thickness of the electron transport layer and the hole blocking layer are both 20-100 nm, and the distance between them is 0.5-2 mm.

[0008] Preferably, β- Ga 2 O 3 The film layer thickness is 500-1000nm.

[0009] Preferably, the metal electrode is circular and made of gold, platinum or silver.

[0010] Preferably, the thickness of the metal electrode is 10-80 nm and the diameter is 10-200 μ m.

[0011] The second object of the present invention is to provide a method for preparing a gallium oxide-based laminated structure ultraviolet detector, which specifically comprises the following steps: S1. Clean the gallium nitride single crystal substrate, place it in a tube furnace, remove the residual gas in the tube furnace, introduce high-purity oxygen, and then heat it; after heating, cool it to room temperature, stop introducing oxygen, and form a GaON thin film layer; S2. The oxidized gallium nitride single crystal substrate is placed in an acid solution for treatment, and then treated with plasma; a low-temperature thermal annealing treatment is performed to repair lattice damage; S3. Epitaxial growth on the substrate surface after treatment in step S2 β- Ga 2 O 3 Thin film layer; S4. β- Ga 2 O 3 Thin film layers The electron transport layer and the hole blocking layer were deposited by magnetron sputtering technology; S5. Use a mask to reserve the middle part of the electron transport layer and the hole blocking layer, and use ion sputtering technology to evaporate the metal electrode in the middle part.

[0012] Preferably, step S3 specifically includes the following sub-steps: S301. First, epitaxially grow a layer with a thickness of 30-60nm on a gallium nitride single crystal substrate. β- Ga 2 O 3 , the organic source is triethylgallium, the organic source temperature is set at 0-10°C, the organic source flow rate is maintained at 1-4sccm, the temperature is controlled at 600-700°C, and the growth time is 30-50min; S302. Close the inlet and outlet valves of the organic source, stop the oxygen flow, exhaust the air in the chamber, raise the temperature of the organic source to 10-30°C, increase the flow rate of the organic source to 5-15sccm, raise the temperature to between 800-950°C, grow for 120-200 minutes, and form β- Ga 2 O 3 Thin film layer.

[0013] Preferably, in step S1, the oxygen flow rate is 50-100 sccm, and the heating time after heating to 1200-1800° C. is maintained for 120-240 min.

[0014] Preferably, in step S2, the acid solution treatment time is 10-30 min, and the acid solution concentration is 0.5-1.2%; the plasma is oxygen plasma, and the treatment time is 10-50 min; the conditions for the low-temperature thermal annealing treatment are: using an oxygen-nitrogen mixed gas with an oxygen-nitrogen ratio of 7:3, and thermal annealing at 600-900°C for 100-300 min.

[0015] Compared with the prior art, the present invention can achieve the following beneficial effects: The present invention provides a gallium oxide-based laminated structure ultraviolet detector and a preparation method. The method improves the crystal quality of gallium oxide, significantly reduces the internal defects of the film, and the designed laminated structure performs dual regulation on electrons and holes, suppressing the inherent continuous photoconductivity effect of gallium oxide while increasing the ultraviolet photoconductivity gain. The design of this new structure enriches the current research on gallium oxide-based photodetectors, introduces electron transport layers and hole blocking layers into the research of ultraviolet detectors, and proposes a new research idea, namely a method for controlling the electron-hole transport rate. The photodetector device designed by the method of the present invention has a stable structure, the response time of the device can reach the microsecond level, and the fall time is fast, which effectively overcomes the adverse effects of the inherent continuous photoconductivity effect of gallium oxide materials. At the same time, compared with the reported devices, the ultraviolet detection performance of the device is quite excellent. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 It is a schematic structural diagram of a gallium oxide-based laminated structure ultraviolet detector provided according to an embodiment of the present invention.

[0017] Figure 2 It is a large-angle X-ray diffraction pattern (XRD) of a GaON thin film layer structure provided according to an embodiment of the present invention.

[0018] Figure 3 According to an embodiment of the present invention, β- Ga 2 O 3 XRD patterns of the thin film layers.

[0019] Figure 4 This is an image of a GaON thin film layer formed after oxidation of a gallium nitride single crystal substrate provided by an embodiment of the present invention.

[0020] Figure 5 According to an embodiment of the present invention, β- Ga 2 O 3 Cross-sectional images of thin film layers.

[0021] Figure 6 According to an embodiment of the present invention, β- Ga 2 O 3 Surface morphology of the thin film layer.

[0022] Figure 7 According to an embodiment of the present invention, β- Ga 2 O 3 X-ray photoelectron spectroscopy (XPS) of the thin film layer. The figure shows the peak fitting results of O1s.

[0023] Figure 8This is an image showing the variation trend of the wide spectral responsivity of the gallium oxide-based laminated structure ultraviolet detector with wavelength according to an embodiment of the present invention.

[0024] Fig. 9 It is a response time image of multiple cycles of the gallium oxide-based laminated structure ultraviolet detector under ultraviolet illumination conditions provided by an embodiment of the present invention.

[0025] Fig.10 1 is an IV curve of a gallium oxide-based laminated structure ultraviolet detector provided according to an embodiment of the present invention.

[0026] Fig.11 The gallium oxide-based laminated structure ultraviolet detector provided by the embodiment of the present invention has a power of 127 mW / cm 2 It curve under UV light irradiation.

[0027] Fig.12 The gallium oxide-based laminated structure ultraviolet detector provided by the embodiment of the present invention has a power of 1 mW / cm 2 It curve under UV light irradiation.

[0028] Fig.13 The gallium oxide-based laminated structure ultraviolet detector provided by the embodiment of the present invention has a power of 90 nW / cm 2 It curve under UV light irradiation.

[0029] Reference numerals: 1. Gallium nitride single crystal substrate; 2.GaON thin film layer; 3. β- Ga 2 O 3 Thin film layer; 4. ZnO electron transport layer; 5.TiO 2 Hole blocking layer 6.Metal electrode. DETAILED DESCRIPTION

[0030] Hereinafter, embodiments of the present invention will be described with reference to the accompanying drawings. In the following description, the same modules are represented by the same reference numerals. In the case of the same reference numerals, their names and functions are also the same. Therefore, the detailed description thereof will not be repeated.

[0031] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and specific embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and do not constitute a limitation of the present invention.

[0032] The present invention provides a gallium oxide-based laminated structure ultraviolet detector, comprising: a gallium nitride single crystal substrate, a GaON thin film layer located on the surface of the gallium nitride single crystal substrate, and a GaON thin film layer located on the surface of the GaON thin film layer away from the gallium nitride single crystal substrate. β- Ga 2 O 3 Thin film layer, located β- Ga 2 O 3 The ZnO electron transport layer and the TiO layer are symmetrically arranged on the surface of the side of the thin film layer away from the gallium nitride single crystal substrate. 2 Hole blocking layer; ZnO electron transport layer and TiO 2 Metal electrodes are provided on the hole blocking layers; Specifically, β- Ga 2 O 3 The preferred range of film layer thickness is 500-1000nm; Specifically, the ZnO electron transport layer and the TiO 2 The thickness of the hole blocking layer is preferably in the range of 20-100 nm, and the thickness of the ZnO electron transport layer and the TiO 2 The preferred range of the spacing of the hole blocking layer is 0.5-2 mm; Specifically, the metal electrode is circular, with a thickness of 10-80 nm, and the electrode diameter is preferably in the range of 10-200 nm. μ m, the material is one of gold, platinum, silver, etc.

[0033] The present invention provides a method for preparing a gallium oxide-based laminated structure ultraviolet detector, which specifically comprises the following steps: S1. Clean the gallium nitride single crystal substrate and place it in a tube furnace. First, extract the residual gas in the tube furnace by a pump, then introduce high-purity oxygen, and then heat it. After heating, cool the temperature to room temperature, and then stop introducing oxygen to form a GaON thin film layer. Specifically, the oxygen flow rate is 50-100 sccm; the temperature is raised to 1200-1800° C.; the heating time is maintained for 120-240 minutes; S2. The oxidized GaN single crystal substrate is placed in an acid solution for treatment to reduce the GaON thin film layer; the surface is made smoother by plasma treatment, and then low-temperature thermal annealing is performed in a tube furnace to repair lattice damage; Specifically, the acid solution treatment time is 10-30 minutes, the acid solution concentration is 0.5-1.2%, and the acid solution is a dilute hydrochloric acid solution; the plasma is oxygen plasma, and the oxygen plasma surface treatment time is 10-50 minutes; the low temperature after treatment is between 600-900° C., the thermal annealing atmosphere uses an oxygen-nitrogen mixed gas with an oxygen-nitrogen ratio of 7:3, and the annealing time is 100-300 minutes; S3. Epitaxial growth on GaN single crystal substrate by metal organic chemical vapor deposition β- Ga 2 O 3 The thin film layer comprises the following sub-steps: S301. First, epitaxially grow a layer with a thickness of 30-60nm on a gallium nitride single crystal substrate. β- Ga 2 O 3 , triethylgallium (TEGa) was selected as the organic source, the organic source temperature was set at 0-10°C, the organic source flow rate was maintained at 1-4sccm, the temperature was controlled at 600-700°C, and the growth time was 30-50min; S302. Close the inlet and outlet valves of the organic source, stop the oxygen flow, exhaust the air in the chamber, raise the temperature of the organic source to 10-30°C, increase the flow rate of the organic source to 5-15sccm, raise the temperature to between 800-950°C, grow for 120-200 minutes, and form a 300-600nm thick β- Ga 2 O 3 Thin film layer; S4. β- Ga 2 O 3 Thin film layers were deposited by magnetron sputtering technique: ZnO electron transport layer and TiO 2 a hole blocking layer; S5. Use masking to reserve the ZnO electron transport layer and TiO 2 The middle part of the hole blocking layer is deposited with a metal electrode by ion sputtering technology.

[0034] Example 1 Figure 1 The structure of the gallium oxide-based laminated structure ultraviolet detector is shown, including: a gallium nitride single crystal substrate 1, a GaON thin film layer 2 and a β- Ga 2 O 3 The film layer 3, and the β- Ga 2 O 3 The ZnO electron transport layer 4 and the TiO layer 5 are symmetrically arranged on the surface of the thin film layer 3 facing away from the gallium nitride single crystal substrate 1. 2 Hole blocking layer 5; ZnO electron transport layer 4 and TiO 2 A metal electrode 6 is disposed on the hole blocking layer 5 .

[0035] A method for preparing a gallium oxide-based laminated structure ultraviolet detector comprises the following steps: using a metal organic chemical vapor deposition (MOCVD) device to prepare a gallium oxide-based thin film, firstly using a tubular furnace to pretreat an intrinsic gallium nitride substrate, using triethyl gallium as an organic source, using high-purity oxygen as an oxygen source, using high-purity nitrogen as a carrier gas for the organic source, placing the organic source in a cold trap to maintain a constant temperature, controlling the film epitaxy rate by setting the cold trap temperature and the organic source carrier gas flow rate, and realizing two-step growth of gallium oxide by controlling the valve switch.

[0036] The specific steps include: S1. Clean the GaN single crystal substrate and place it in a tube furnace. First, extract the residual gas in the tube furnace through a pump, then introduce high-purity oxygen with an oxygen flow rate of 60 sccm. Then, heat it to 1600°C and maintain the heating time for 180 minutes. After heating, cool it to room temperature and stop introducing oxygen to form a GaON thin film layer.

[0037] S2. The oxidized GaN single crystal substrate is placed in a 1% dilute hydrochloric acid solution for 20 minutes to reduce the GaON thin film layer (i.e., the oxide layer); oxygen plasma treatment is performed for 30 minutes to make the substrate surface smoother, and then low-temperature thermal annealing is performed in a tubular furnace at a temperature of 800°C. The thermal annealing atmosphere is a 7:3 oxygen-nitrogen mixed gas, and the annealing time is 180 minutes.

[0038] S3. Epitaxial growth on GaN single crystal substrate β- Ga 2 O 3 Thin film layer; S301. First, epitaxially grow a layer with a thickness of 30-60nm on a gallium nitride single crystal substrate. β- Ga 2 O 3 TEGa was used as the organic source, the organic source temperature was set at 5°C, the organic source flow rate was maintained at 4 sccm, the temperature was controlled at 700°C, and the growth time was 30 min; S302. Close the inlet and outlet valves of the organic source, stop the oxygen flow, exhaust the air in the chamber, raise the temperature of the organic source to 15°C, increase the flow rate of the organic source to 10 sccm, and raise the temperature to 850°C. After growing for (120) min, a 400 nm thick layer is formed. β- Ga 2 O 3 Thin film layer; Epitaxial Growth β- Ga 2 O 3The thin film layer is deposited by metal organic chemical vapor deposition technology; this step controls the thickness of the epitaxial film by adjusting the organic source temperature and the organic source carrier gas flow rate, and achieves high-quality film growth by cleverly pre-introducing the organic source and then slowly and linearly increasing the oxygen flow rate.

[0039] S4. β- Ga 2 O 3 Thin film layers were deposited by magnetron sputtering technique: ZnO electron transport layer and TiO 2 Hole blocking layer; ZnO electron transport layer and TiO 2 The thickness of the hole blocking layer is 80nm and 50nm respectively, the ZnO electron transport layer and TiO 2 The spacing of the hole blocking layer is 1 mm.

[0040] S5. Use masking to reserve the ZnO electron transport layer and TiO 2 The middle part of the hole blocking layer is deposited with a metal electrode by ion sputtering technology; the metal electrode is made of gold, has a circular shape, a thickness of 50nm, and an electrode diameter of 100 μ m.

[0041] The photoelectric performance of the gallium oxide-based stacked structure UV detector was tested. For the relationship between the wavelength and responsivity of the device, a high-pressure mercury lamp and a monochromator were used to adjust the wavelength from 230nm to 550nm, and then the source meter was used to record the photocurrent value and calculate the responsivity; for the IT characteristics of the device, a 246nm tunable laser was applied for testing.

[0042] Figure 2 The XRD spectrum of the GaON thin film layer structure after high-temperature oxidation of GaN is shown. In addition to the peaks of GaN itself, there are also corresponding β The peak position of the gallium oxide phase.

[0043] like Figure 3 As shown in Figure 2, we can see that the XRD spectrum of gallium oxide epitaxially grown by controlling the precursor reaction conditions belongs to β -Ga 2 O 3 The three characteristic peaks are high in position and narrow in line width, indicating that the surface epitaxial film has a high crystalline quality.

[0044] Figure 4 and Figure 5The figures show the cross-sectional image of GaN after high-temperature oxidation and the total film thickness after epitaxial growth. It can be seen that the cross-sectional image of GaN after oxidation is relatively rough. Although some researchers have reported GaN high-temperature oxidation epitaxial growth, they have ignored the uncertainty of this oxidation, resulting in low quality of GaN crystals after epitaxy. The present invention uses a variety of surface treatment technologies to improve the quality of epitaxially grown films.

[0045] To further study the epitaxy β- Ga 2 O 3 The surface morphology of the film layer was observed by atomic force microscopy. Figure 5 As shown, through research and analysis, the root mean square roughness of the surface is 0.45nm.

[0046] With the help of XPS technology β- Ga 2 O 3 The oxygen vacancy concentration inside the film layer is quantitatively measured. Figure 7 It is the fitting result of the O1s peak after carbon calibration. The binding energy of 530.5eV is defined as lattice oxygen, 531.5eV is defined as oxygen vacancies, and 532.5eV is defined as adsorbed oxygen. Among them, we are most concerned about the proportion of oxygen vacancies. The fitting results show that the concentration of oxygen vacancies is 17%, showing β- Ga 2 O 3 The oxygen defect content inside the film layer is low.

[0047] Figure 8 The peak responsivity of the device can reach 10 to the cube, far exceeding the responsivity of similar devices. Fig. 9 It can be observed that the response time of the device is in the order of 1ms, and is even expected to reach the order of μs, which means the response speed is relatively fast.

[0048] Fig.10 The IV curve of the UV detector shows that the dark current of the device is very low, only 64 pA at 10 V. At the same time, in order to test the detection performance of the device under UV light of different intensities, the pulsed laser is adjusted to obtain 127 mW / cm 2 The UV lamp was adjusted to obtain 1 mW / cm 2 , 90 nW / cm 2 The device was irradiated with ultraviolet light and the It curves of the device under different light intensities were measured (the test voltage was 10 V). Fig.11 , Fig.12 , Fig.13 , the photosensitive area of ​​the device is 0.5 mm2 .

[0049] The device is at 127 mW / cm 2 When the device is exposed to ultraviolet light, a 100 ohm load resistor is connected in series with the device, and then the voltage division on the load resistor is tested. When the device is at the peak response, the voltage division of the load resistor is 6.6V. By calculation, the voltage division of the device is 3.4V, the resistance of the device is 51.5 ohms, and the equivalent light response of the device is 306 A / W. The device is at 1 mW / cm 2 , 90 nW / cm 2 When the device is irradiated with ultraviolet light, the current of the device is directly measured and the responsivity of the device is calculated.

[0050] The calculated results show that the 2 , 1 mW / cm 2 , 90 nW / cm 2 ) have responsivities of 306 A / W, 355 A / W, and 364 A / W, respectively; and response times of 3.8 μs, 30 ms, and 800 ms, respectively.

[0051] The principle of the present invention is briefly described as follows: the method is to treat the gallium nitride single crystal substrate in a high-temperature oxygen-rich environment so that the nitrogen atoms within the GaN surface thickness of about 10-50nm are replaced by oxygen atoms, or more oxygen atoms enter the internal gaps of the GaN unit cell to form a GaON structure; on this basis, epitaxial growth of gallium oxide is carried out, and the lattice mismatch between the two is much smaller than that of direct growth on GaN. Acid treatment and surface treatment are carried out on the oxidized single crystal substrate to make the substrate surface as flat as possible, and then low-temperature annealing is used to repair the damaged lattice to further reduce the surface dangling bonds. Then a thinner layer of gallium oxide is grown on the GaON as a buffer layer, and then a thicker gallium oxide is grown. The two-step growth method combined with substrate treatment can obtain crystals with better quality. β- Ga 2 O 3 The film is also grown on top of zinc oxide and titanium dioxide by magnetron sputtering. Considering that ZnO and TiO 2The bandgap widths of the two are 3.37eV and 3.2eV, so it is necessary to retain ultraviolet-sensitive gallium oxide between the two materials as a source of photoconductivity gain. Zinc oxide is a cubic wurtzite structure, and the atomic arrangement in its unit cell is very suitable for the up and down transmission of electrons inside zinc oxide, which is a relatively mature electron transport layer; titanium dioxide is a rutile structure, which has a certain blocking effect on holes in the vertical direction. It is reported that it can be used as an intermediate layer in the detector to effectively block the transport process of holes; by combining the electron transport layer and the hole blocking layer, the movement speed of electrons in the material can be increased, and the life span of minority carrier holes in gallium oxide can be increased. For ultraviolet detectors, unlike the previous MSM structure, another layer of material is added between the electrode and gallium oxide. On the one hand, it speeds up the transit time of free electrons between the positive and negative electrodes, making the device's response time faster, and on the other hand, it hinders the one-way transit of holes, increases the photoconductivity gain, and makes the device more responsive.

[0052] It should be understood that the various forms of processes shown above can be used to reorder, add or delete steps. For example, the steps described in the disclosure of the present invention can be performed in parallel, sequentially or in different orders, as long as the desired results of the technical solution disclosed in the present invention can be achieved, and this document does not limit this.

[0053] The above specific implementations do not constitute a limitation on the protection scope of the present invention. It should be understood by those skilled in the art that various modifications, combinations, sub-combinations and substitutions can be made according to design requirements and other factors. Any modification, equivalent substitution and improvement made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A gallium oxide-based laminated structure ultraviolet detector, characterized in that: include: Gallium nitride single crystal substrate, GaON thin film layer and β- Ga2O3 thin film layer, and β- An electron transport layer and a hole blocking layer are symmetrically arranged on the surface of the Ga2O3 thin film layer on the side away from the gallium nitride single crystal substrate; metal electrodes are arranged on both the electron transport layer and the hole blocking layer.

2. The gallium oxide-based laminated structure ultraviolet detector according to claim 1, characterized in that: The material of the electron transport layer is ZnO, and the material of the hole blocking layer is TiO2.

3. The gallium oxide-based laminated structure ultraviolet detector according to claim 2, characterized in that: The thickness of the electron transport layer and the hole blocking layer are both 20-100 nm, and the distance between them is 0.5-2 mm.

4. The gallium oxide-based laminated structure ultraviolet detector according to claim 1, characterized in that: Said β- The thickness of Ga2O3 thin film layer is 500-1000nm.

5. The gallium oxide-based laminated structure ultraviolet detector according to claim 1, characterized in that: The metal electrode is circular and made of gold, platinum or silver.

6. The gallium oxide-based laminated structure ultraviolet detector according to claim 5, characterized in that: The thickness of the metal electrode is 10-80nm and the diameter is 10-200 μ m.

7. The method for preparing a gallium oxide-based laminated structure ultraviolet detector according to any one of claims 1 to 6, characterized in that: The specific steps include: S1. Clean the gallium nitride single crystal substrate, place it in a tube furnace, remove the residual gas in the tube furnace, introduce high-purity oxygen, and then heat it; after heating, cool it to room temperature, stop introducing oxygen, and form a GaON thin film layer; S2. The oxidized gallium nitride single crystal substrate is placed in an acid solution for treatment, and then treated with plasma; a low-temperature thermal annealing treatment is performed to repair lattice damage; S3. Epitaxial growth on the substrate surface after treatment in step S2 β- Ga2O3 thin film layer; S4. β- Ga2O3 thin film layers were deposited as electron transport layers and hole blocking layers by magnetron sputtering technology; S5. Use a mask to reserve the middle part of the electron transport layer and the hole blocking layer, and use ion sputtering technology to evaporate the metal electrode in the middle part.

8. The method for preparing a gallium oxide-based laminated structure ultraviolet detector according to claim 7, characterized in that: The step S3 specifically includes the following sub-steps: S301. First, epitaxially grow a layer with a thickness of 30-60nm on a gallium nitride single crystal substrate. β- Ga2O3, triethylgallium is selected as the organic source, the organic source temperature is set at 0-10°C, the organic source flow rate is maintained at 1-4sccm, the temperature is controlled at 600-700°C, and the growth time is 30-50min; S302. Close the inlet and outlet valves of the organic source, stop the oxygen flow, exhaust the air in the chamber, raise the temperature of the organic source to 10-30°C, increase the flow rate of the organic source to 5-15sccm, raise the temperature to between 800-950°C, grow for 120-200 minutes, and form β- Ga2O3 thin film layer.

9. The method for preparing a gallium oxide-based laminated structure ultraviolet detector according to claim 8, characterized in that: In the step S1, the oxygen flow rate is 50-100 sccm, and the heating time after heating to 1200-1800° C. is maintained for 120-240 minutes.

10. The method for preparing a gallium oxide-based laminated structure ultraviolet detector according to claim 9, characterized in that: In the step S2, the acid solution treatment time is 10-30 minutes, and the acid solution concentration is 0.5-1.2%; the plasma is oxygen plasma, and the treatment time is 10-50 minutes; the conditions for the low-temperature thermal annealing treatment are: using an oxygen-nitrogen mixed gas with an oxygen-nitrogen ratio of 7:3, and thermal annealing at 600-900°C for 100-300 minutes.

Citation Information

Cited By

  • Vertical-structure GaN-based p-i-n type ultraviolet detector on metal molybdenum substrate

    CN121174618A

  • Vertical structure GaN-based p-i-n type ultraviolet detector on metal molybdenum substrate

    CN121174618B